Do shopping anxiety and data leakage risks matter to e-commerce customers? Evidence from the largest economy in Southeast Asia - Yudi Sutarso; Bagus Suminar; Aniek Maschudah Ilfitriah (Jurnal Manajemen dan Pemasaran Jasa, 2024)
Shopping anxiety and data leakage risk are issues in e-commerce in Indonesia, where the House of Representatives issued the Personal Data Protection Law in 2022, which regulates personal data protection.    This study explores the effects of shopping anxiety, data leakage risk, e-service quality, and attitude on intention to reuse e-commerce.  An electronic survey was employed to collect data, and the population is customers who’ve made purchasing activities on Shopee.  This study used purposive sampling to select respondents by the criteria such as customers at least six months as customers, aged 17 and over, and having purchased at least once in the last month.  Questionnaires were distributed to 435 users, where respondents’ answers were based on a seven-point Likert scale, and the data analysis was carried out using PLS-SEM. The findings indicated that e-service quality positively influences attitudes and intention to reuse e-commerce but negatively affects shopping anxiety and data leakage risk.  Moreover, shopping anxiety and data leakage risk moderate the relationship between e-service quality and intention to reuse e-commerce, and gender moderates the relationship between shopping anxiety and intention to reuse e-commerce. Furthermore, the results raise awareness among e-commerce managers and policymakers about the negative impact of shopping anxiety and data leakage risk in e-commerce consumers.